Ação neuro-muscular do veneno crotálico: dados preliminares - Silva, Maria Dorvalina [UNESP]; Resende, Luiz Antonio de Lima [UNESP]; Ueda, Anete Kimuni [UNESP]; Barraviera, Benedito [UNESP]; Mendes, R.P. [UNESP]; Montenegro, Mário Rubens G. [UNESP] (Academia Brasileira de Neurologia (ABNEURO), 1996)
Estudamos 6 pacientes, 2 cães e um coelho com intoxicação crotálica. Avaliamos a condução nervosa periférica sensitiva e motora, a transmissão neuromuscular e eletromiografias. As biópsias de músculo foram processadas por histoquímica. Os 6 pacientes apresentaram mononeuropatia sensitiva no nervo periférico adjacente ao local da inoculação do veneno e encontramos evidências histoquímicas de miopatia mitocondrial. Os defeitos da transmissão neuromuscular foram mínimos. A maioria dos autores admite que veneno crotálico determina síndrome miastênica. Nossos achados indicam que ptose palpebral, facies miastênico e fraqueza muscular observados após acidente crotálico, correspondem provavelmente a miopatia mitocondrial, muitas vezes transitória e reversível.

We studied 6 patients and 2 dogs that have been bitten by South American rattlesnake Crotalus durissus terrificus and one rabbit inoculated with crotalid venom. We analized sensory and motor peripheral nerve conduction, repetitive stimulation for studying neuromuscular transmission and electromyographies. Muscle biopsies were processed by histochemistry. All patients had peripheral mononeuropathy of the closest sensitive nerve to the area of snakebite. The neuromuscular transmission alterations were minimal. Muscle histochemistry of 4 patients, 2 dogs and 1 rabbit showed findings of mitochondrial myopathy. The majority of authors admit that crotalid venom causes myastenic syndrome. Our findings suggest that palpebral ptosis, myastenic facies and muscular weakness observed after crotalid poisoning are, probably, due to transient and reversible mitochondrial myopathy. As far as we know, this is the first report on the ability of the venom of this rattlesnake to cause local sensitive mononeuropathy and the first muscle histochemistry showing mitochondrial myopathy in humans poisoned by crotalid venom.
Neuromuscular action of crotalid venom: preliminar data
Keywords: veneno crotálico; mononeuropatia sensitiva; miopatia mitocondrial; crotalid venom; sensory mononeuropathy; mitochondrial myopathy